PERTANGGUNG JAWABAN ADVOKAT TERHADAP KLIEN BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2003 - Ibnu Qudama; Zainuddin Hasibuan; Fauziah Lubis (Smart Education, 2023)
Abstract: The development of society and the increasingly complex relations that exist between them, in the social and economic fields, need to be followed by the issuance of various legal regulations in order to maintain order in these relations. The complexity of the applicable legal rules makes these rules not easily understood by the public so that a code of ethics is needed to keep advocates serving the interests of society and the trust that has been given by society. Advocates must protect all things that are known or obtained from their clients because of their work ties, unless otherwise stipulated by law; Advocates are prohibited from holding other positions that are contrary to the requirements of their obligations and the degree of their work. This study aims to find out how the form of supervision from an advocate organization regarding the implementation of the obligation to provide legal services to clients by advocates and how good faith in Article 16 of Law No. 18 of 2003 concerning Advocates. The research method used in this paper is a research method that is carried out using a normative juridical approach, where data collection is carried out using the Library Research method. The obligation of an advocate in carrying out his work obligations is prohibited but the treatment of consumers stems from gender, religion, politics, generation, ethnicity, or social and customary backgrounds. Advocates cannot be identified with their clients in defending consumer problems by the rightful parties and or or citizens.Keywords: advoca; client; responsibility; UUD Abstrak: Perkembangan masyarakat yang cukup pesat dan makin kompleksnya relasi relasi yang terjalin diantara mereka, baik di bidang sosial maupun ekonomi perlu diikuti dengan keluarnya berbagai aturan hukum guna untuk menjaga ketertiban dalam relasi tersebut. Rumitnya aturan hukum yang berlaku membuat aturan tersebut tidak mudah dipahami oleh masyarakat sehingga kode etik di perlukan untuk menjaga agar advokat mengabdi kepada kepentingan masyarakat dan kepercayaan yang telah diberikan oleh masyarakat. Advokat harus melindungi seluruh suatu yang dikenal ataupun didapat dari Kliennya sebab ikatan pekerjaannya, melainkan didetetapkan lain oleh Hukum; Advokat dilarang menggenggam kedudukan lain yang berlawanan dengan kebutuhan kewajiban serta derajat pekerjaannya. Studi ini bertujuan untuk mengetahui bagaimana bentuk pengawasan dari organisasi advokat terhadap pelaksanaan kewajiban pemberian jasa hukum terhadap klien oleh advokat dan bagaimana itikad baik dalam Pasal 16 Undang-undang No. 18 Tahun 2003 Tentang Advokat. Metode penelitian yang digunakan dalam penulisan ini adalah metode penelitian yang dilakukan dengan pendekatan yuridis normatif, dimana pengumpulan data dilakukan dengan metode Library Research. Kewajiban advokat dalam melaksanakan kewajiban pekerjaannya dilarang melainkan perlakuan kepada konsumen bersumber pada gender, agama, politik, generasi, suku bangsa, ataupun kerangka balik sosial serta adat. Advokat tidak bisa diidentikkan dengan kliennya dalam membela masalah konsumen oleh pihak yang berhak ataupun warga.Kata kunci: advokat; klien; tanggung jawab; UUD